Fighting governmental corruption in Pakistan : an evaluation of anti-corruption strategies - Ulain, Noor (Array, 2020)
Corruption remains a persistent problem in both developed and developing countries. Statistics provide evidence that Pakistan faces the menace of corruption. The recently released Corruption Perception Index (CPI) for 2019 by Transparency International (TI) ranks Pakistan as the 120th country out of a total of 180. In 1995 Pakistan used to be the second most corrupt country in the world. Moreover, TI’s Global Corruption Barometer for 2017 shows that 40–50 per cent of the respondents have given a bribe to get a public service in Pakistan. The Global Competitiveness Reports (2016, 2017, and 2018) released by the World Economic Forum in Switzerland have declared corruption to be the topmost problematic factor when doing business in Pakistan. Corruption is a public problem and relevant academic literature holds the dominant view that it obstructs economic development. It increases the direct costs of firms through bribery. It encourages bureaucratic red tape and corrupts the institutions of contract enforcement and property rights protection. Although corruption and anti-corruption have long been research topics in the social sciences, little has been done about the evaluation of anti-corruption strategies. Anti-corruption efforts are required where corruption prevails. With this in view, the study aims to ascertain the opinion of policy professionals regarding different anti-corruption strategies. Data on 26 anti-corruption strategies were collected through a self-administered questionnaire from 100 policy professionals working in 12 different policy institutes. The results have found slight differences between the mean scores for anti-corruption strategies, depicting a certain level of effectiveness for each strategy. Harsher punishments for corrupt persons and legal protection for whistleblowers informing about persons involved in corruption are the strategies that had the highest mean scores of 4.07 and 4.04 respectively.